DIGITOOLS - the future of open digital education (Pubmet, 2022)
The Multiplier Events will see the participation of stakeholders, international experts, and academia. The aim of this regional multiplier event is to bring the results of the research conducted within the DIGITOOLS project. The workshop will also discuss the future of digital education in universities and European frameworks in the field of digital education. Special focus is on the role of Universities in the effective implementation of digital learning, Open educational resources and open access to resources.The crisis generated by the COVID 19 pandemic has forced European universities to move their teaching activities to the online environment. Although most Higher Education Institutions have implemented E-Learning platforms years ago, the teaching staff are now experiencing difficulties in using these platforms and in creating and adapting the course content, needed to quickly adapt to a fast evolving and complex situation.DIGITOOLS is a project aimed at introducing enhanced digital tools and methods to help university staff deliver quality education through online means. The DIGITOOLS project will develop five Intellectual Outputs which will support the teaching staff from Higher Education Institutions to acquire the skills and competencies needed to create and deliver high quality online courses, including blended teaching.The role of university libraries will be crucial in this project, as they will have to adapt their services and provide digital learning materials as well as information and digital skills training, both to teaching staff and students. As a result of the DIGITOOLS project, the universities will be able to provide, through teaching staff and libraries, high quality online training courses, with a focus on subject – specific teaching. The project brings together seven Higher Education Institutions and one consulting SME, specialized in digitization, from seven countries and will focus on the implementation of online and blended teaching, encouraging, at every step, the unitary practice.